EV Range Extender in a Two-Battery HEECS Chopper-Based Powertrain - Ayataro Tamura; Takayuki Ishibashi; Atsuo Kawamura (World Electric Vehicle Journal, 2019)
This paper first presents a new powertrain based on a two-battery High-Efficiency Energy Conversion System (HEECS) chopper that is suitable for electric vehicles (EVs). The HEECS chopper is based on the principle of a partial power conversion circuit, and the overall efficiency is over 99% in a wide load range. The efficiency of this powertrain was measured in the steady state by two types of powertrains, a non-chopper powertrain and an HEECS chopper-based powertrain, using a motor test bench. On the basis of these data, several driving tests, such as the Worldwide-harmonized Light vehicles Test Cycle (WLTC), were simulated, and four driving cycle patterns were included. A 6.4% reduction in energy consumption was observed in WLTC low mode compared with the energy consumed by the non-chopper powertrain in the experiments. Thus, the HEECS chopper-based powertrain is more suitable for low-speed driving ranges than high-speed ranges.